Nocturia: its characteristics, diagnostic algorithm and treatment (2022)
Nocturia is the complaint that an individual has to wake up at night one or more times to urinate. It is a frequent condition among older adults and entails detrimental effects with regard to sleeping, sexual activity, comfort, depression, mental function and vitality. It is clinically important to distinguish it from global polyuria, defined as a urinary rate ≥ 125 ml/h (3000 ml/day), as well as from nocturnal polyuria, which is an abnormally large volume of urine during sleep associated with a decreased daytime urine production. A Frequency Volume Chart (FVC), overnight water deprivation test with renal concentrating capacity test, and the nocturnal bladder capacity index are some of the methods that help establish the underlying pathology of this condition and hence define an adequate treatment plan.